2002
DOI: 10.1074/jbc.m111302200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Human STAT1Gene Regulatory Element

Abstract: WAF/CIP (4, 5) and cell death via expression of caspases (6). Our work (7,8) and that of others (9 -11) revealed that STAT1 expression is deficient in a number of different human cancer cell types resistant to type I IFNs in antiproliferative and antiviral assays. STAT1 has also been shown to be the target of viral proteins inhibiting IFN signaling responses (12). In addition, STAT1 expression in tumor cells has been shown to be important for tumor elimination by immune surveillance mechanisms (13) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Others have shown that early induction of IRF-1 requires rapid translocation of activated STAT1 to the nucleus (29). Newly synthesized IRF-1 permits additional synthesis of STAT1 (10). The increased IRF-1 and STAT1 contribute to the induction of late IFN-␥-stimulated genes, which are regulated by multiple transcription factors, and by autocrine feedback (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have shown that early induction of IRF-1 requires rapid translocation of activated STAT1 to the nucleus (29). Newly synthesized IRF-1 permits additional synthesis of STAT1 (10). The increased IRF-1 and STAT1 contribute to the induction of late IFN-␥-stimulated genes, which are regulated by multiple transcription factors, and by autocrine feedback (22).…”
Section: Discussionmentioning
confidence: 99%
“…Genes-Interferon regulatory factor-1 (IRF-1) is an early STAT1-dependent IFN response gene, the product of which, in a feed-forward positive feedback loop, directly activates the STAT1 gene promoter (10). Newly synthesized STAT1 and IRF-1 then contribute to the induction of other late IFN-␥-stimulated genes (22).…”
Section: Inactivation Of Mtor Enhances the Induction Of Early Ifn-␥-smentioning
confidence: 99%
See 1 more Smart Citation
“…8B), a transcription factor with tumor suppressor properties that has been shown to revert the transformed phenotype of Ras-transformed cells in vitro and in vivo (73) and plays a major role in transcriptional activation of STAT1 (52). Mouse embryonal fibroblasts homozygous for IRF-1 deficiency undergo transformation upon expression of an activated form of Ha-Ras and no longer require a cooperating oncogene, such as c-myc (74).…”
Section: Fig 3 Concentration-dependent Induction Of Stat2 By Ifn␥ Imentioning
confidence: 99%
“…A number of studies have shown that various cell types, including primary chronic lymphocytic leukemia, human trophoblast, melanoma, and acute promyelocytic leukemia, are resistant to the actions of IFN because the induction of p48 protein is defective (9 -12). Additionally, it has been argued that IFN-␥ priming up-regulates p48-enhanced antiviral and antitumor effects of class I IFNs on IFN-resistant cells (13,14). Furthermore, recent studies have shown that p48 protein also binds to virus-inducible elements within the IFN-␣/␤ promoters.…”
mentioning
confidence: 99%